Teaching strategies for recognizing, using and mastering irregular verbs in affirmative and interrogative form in the students of first baccalaureate. - Egas Fajardo, Amanda Milena (Machala : Universidad Técnica de Machala, 2017)
The following research talks about the importance of English in student life, and how teachers can use some strategies for teaching that could be more efficient in the construction of knowledge of students. As we know English language is very wide so in this document we specify the teaching strategies of irregular verbs. The only way of learning irregular verbs is by heart, this is maybe why not every student finds success learning it, but also because of what we have mentioned in this work to an expert of the theme, Noam Chomsky’s theory is also immerge explaining how memorizing sometimes can help us, and be as important as teachers to make our students learn. For more help on how to make an interactive and different and dynamic class, you can take some ideas of ‘warms – ups’ to use it for your own and practice with your class from “czifra 2012” quote given here in the form of games, a big variety of them that also you can use it modifying for other topics, all of that games are proposed in this document obviously and also according to our research project and main topic of irregular verbs.
Keywords: VERBS; NOAM CHOMSKY; MEMORIZING; BACCALAUREATE